Penurunan Kata dengan Morfem Unik - Nazir, Yuniar Nuri (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
This study aims to describe the process and characteristics of word derivation with unique morphemes in Indonesian. The research is motivated by the limited specific studies on this morphological phenomenon, necessitating a comprehensive description to enrich the linguistic treasury of Indonesia. A qualitative descriptive approach was employed, with structural theory as the analytical foundation. Data were collected through field survey, observation, and elicitation methods in Suralaga District, East Lombok, while data analysis used the distributional method with substitution techniques. The results indicate that the process referred to as